Electrodialysis-based zero liquid discharge in industrial wastewater treatment - Havelka, Jan; Fárová, Hana; Jiříček, Tomáš; Kotala, Tomáš; Kroupa, Jan (Water science and technology, 2019)
Over the past few decades, reverse osmosis (RO) has been the dominant technology employed in zero liquid discharge (ZLD) systems for industrial wastewater treatment (WWT). However, RO is limited to a maximum operating salinity of about 75 g kg-1. Electrodialysis (ED) is a potentially attractive option as it can achieve much higher concentrations, thereby reducing the capacity and energy demand of the subsequent evaporation step. Feed-and-bleed experiments were undertaken on a laboratory-scale ED stack using a series of model solutions based on the most common inorganic salts with the aim of determining maximum achievable concentrations. The maximum salt concentration achievable via ED ranged between 104.2 and 267.6 g kg-1, with levels predominantly limited by water transport. In addition, a straightforward review of how ED incorporation can affect ZLD process economics is presented. The operational cost of an ED-based ZLD system for processing RO retentate was almost 20% lower than comparable processes employing high-efficiency RO and disc tubular RO. As the ED-based ZLD system appears economically preferable, and as maximum achievable concentrations greatly exceeded RO operating limits, it would appear to be a promising approach for bridging the gap between RO and evaporation, and may even eliminate the evaporation step altogether.
Keywords: salinita; chlorid sodný; Membranes, Artificial; filtrace; Osmosis; Sodium Chloride; odpad tekutý - odstraňování; čištění vody; Water Purification; Salinity; Filtration; membrány umělé; Waste Disposal, Fluid; osmóza; Wastewater; Waste Water; odpadní voda